LncRNA affects epigenetic reprogramming of porcine embryo development by regulating global epigenetic modification and the downstream gene SIN3A - Zhang, Daoyu; Zhou, Yongfeng; Huang, Rong; Zhai, Yanhui; Wu, Di; An, Xinglan; Zhang, Sheng; Shi, Lijing; Li, Qi; Kong, Xiangjie; Yu, Hao; Li, Ziyi (Frontiers in Physiology, 2022)
The study of preimplantation development is of great significance to reproductive biology and regenerative medicine. With the development of high-throughput deep sequencing technology, it has been found that lncRNA plays a very important role in the regulation of embryonic development. In this study, key lncRNAs that regulate embryo development were screened by analyzing the expression pattern of lncRNA in porcine in vivo fertilization (IVV) embryos. By knocking down lncRNA expression in in vitro fertilization (IVF) embryos, we investigated its function and mechanism of regulating embryonic development. The results showed that the expression pattern of lncRNA was consistent with the time of gene activation. The lncRNAs were highly expressed in 4-cell to blastocyst stage, but barely expressed in oocytes and 2-cell stage. So, we speculated this part of lncRNAs may regulate gene expression. LncRNA LOC102165808 (named lncT because the gene near this lncRNA is TFAP2C) was one of them. The knockdown (KD) of lncT inhibited embryonic development, resulting in decreased H3K4me3, H3K4me2, H3K9me3, and increased DNA methylation. Meanwhile, the RNAseq showed SIN3A was the top decreased gene in lncT-KD embryos. There was a severe blastocyst formation defect in SIN3A-KD embryos. Both lncT and SIN3A could affect NANOG and induce more cell apoptosis. In conclusion, the knockdown of lncT inhibits embryonic development by regulating H3K4me3, H3K4me2, DNA methylation, pluripotency gene and apoptosis, and SIN3A is one of the downstream genes of lncT in regulating embryonic development.